Obesity and hypertension in children and adolescents: a narrative review (International Seven Journal of Health Research, 2023)
One of the major public health problems today is overweight. Obesity is already known to be an important risk factor for several chronic noncommunicable diseases, which are allocated among endocrine-metabolic diseases, cardiovascular diseases, and neoplasms¹. The World Health Organization released in its World Obesity Report 2022 a projection in which it estimates that by 2030 the world will go through an obesity epidemic and Brazil will have 7.7 million obese children, and it also estimates that about 23% of children aged 5 to 9 years and 18% of adolescents aged 10 to 19 years will be affected by this disease. Regarding cardiovascular diseases, arterial hypertension also constitutes one of the most important risk factors that induce these conditions. Currently, with the mandatory measurement of BP starting at three years of age or even earlier in the presence of risk factors for children, there is an increase in blood pressure levels in the pediatric age group, raising a warning sign for global health, since it can be a marker of the onset of target organ damage.  Overweight is a significant predictor of high BP in this population, besides obesity being a known important risk factor for the acquisition of cardiovascular diseases.